Decreases in performance observed after covid-19 infection in high school female soccer players - Wilson, A.; Carlson, L. M.; Norton, C.; Bruce, W. D. (International Journal of Athletic Therapy & Training, 2022)
This case report retrospectively reviewed competition sprinting performances by a cohort of eight female high school soccer players before and after the incidence of coronavirus 2019 (COVID-19). Performances were split into COVID-19-positive and COVID-19-negative groups, and metrics were collected using a global positioning system for each player during each game. An apparent decrease of 21.13% was found in the COVID-19-positive group`s performances in distance sprinted per game in contrast to an increase of 8.43% for the COVID-19-negative group`s performances. Results suggest patient-athletes experience decreases in intense sprinting performances following COVID-19 infection.